Cyberculture and digital hygiene as essential competencies of a modern teacher of informatics - Kozub Attila; Stoika Myroslav; Sztojka Miroszláv; Стойка Мирослав (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. In today’s digital society, where information and communication technologies (ICT) have penetrated all areas of life, cyberculture and digital hygiene have become essential competencies for informatics teachers. A modern teacher must not only possess technical skills in programming or working with digital tools, but also be capable of creating an environment where the use of technology is safe, ethical, and conscious, minimizing the risks of cyber threats, data loss, or information overload. One of the key components is digital hygiene as a practical skill: protecting personal and student data, using strong passwords, being aware of online fraud, and regularly updating software. Without such knowledge, a teacher risks creating vulnerable situations within the educational process. At the same time, cyberculture also encompasses ethical, social, and psychological aspects: respecting copyright, following communication ethics in social networks and forums, critically evaluating information sources, and developing what can be called digital ethics. In other words, fostering cyberculture means that a teacher does not simply master a tool, but understands how to use it responsibly and how its use affects students and the educational environment as a whole. Research in Ukraine confirms that digital literacy—which is a component of both cyberculture and digital hygiene—is actively recognized as part of the professionally important competencies of future teachers. For example, in the article by Henseruk H. [1], it is emphasized that developing digital competencies through courses in cybersecurity, media education, and ICT use is essential. Another source, by Stoika O. [2], indicates that postgraduate teachers often have general digital skills, but their digital hygiene and cyberethics are less developed, which reduces their ability to respond effectively to challenges related to data security and online environments. In teaching informatics, it is advisable to implement methodological modules that combine digital hygiene and cyberethical practices: educational tasks, case analyses of privacy or ethical violations online, and projects in which students and teachers work together to protect information or create safe digital environments. This approach contributes not only to technical preparation but also to cultivating responsible digital users and citizens. A systematic approach is also important: this competency should be integrated into teacher training programs, including both theoretical knowledge and practical exercises, self-education, the use of digital environments, and the assessment (monitoring) of teachers’ digital hygiene and cyberculture levels. Ultimately, cyberculture and digital hygiene as core competencies of modern informatics teachers contribute to improving the quality of the educational process, reducing security risks, enhancing interaction in digital environments, and fostering students’ and parents’ trust in the use of information technologies in learning.
Teljes kiadvány: https://kme.org.ua/uk/publications/rol-bezpeki-v-transkordonnomu-ta-mizhnarodnomu-spivrobitnictvi/
Keywords: information and communication technologies (ICT); cyberculture; teaching informatics